Фармакотерапия хронического гепатита С, ассоциированного с аутоиммунным тиреоидитом = Pharmacotherapy of chronic hepatitis C, associated with autoimmune thireoiditis - T. V. Tregub (Kazimierz Wielki University, 2016)
Тregub Т. V. Фармакотерапия хронического гепатита С, ассоциированного с аутоиммунным тиреоидитом = Pharmacotherapy of chronic hepatitis C, associated with autoimmune thireoiditis. Journal of Education, Health and Sport. 2015;5(11):705-710. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.44254 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A705-710 http://pbn.nauka.gov.pl/works/687190 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015.   УДК: 616.36-002.12-06:616.43]-085.281   ФАРМАКОТЕРАПИЯ ХРОНИЧЕСКОГО ГЕПАТИТА С, АССОЦИИРОВАННОГО С АУТОИММУННЫМ ТИРЕОИДИТОМ   PHARMACOTHERAPY OF CHRONIC HEPATITIS C, ASSOCIATED WITH AUTOIMMUNE THIREOIDITIS   Т. В. Трегуб Т. V. Тregub   Одесский национальный медицинский университет, г. Одесса, Украина Odessa National Medical University, Odessa, Ukraine   Summary Aim of work - to pick up effective and safe therapy for treatment of chronic hepatitis With, associated with autoimmune thireoiditis. Researches passed on the base of different hospitalsOdessaduring 3 years. It was inspected 28 patients with chronic НСV, associated with autoimmune thireoiditis, in age 18-53. It is investigational, that adding of phosphoglive to safe antiviral therapy of chronic hepatitis With, associated with autoimmune thireoiditis, considerably improves efficiency of treatment, namely - clinical flow of disease, dynamics of laboratory indexes (hepatic tests and data of thyroid panel), virologic answer as reduction of the virologic loading RNA HCV, dynamics of ultrasonic structure of organs of abdominal region and thyroid and accordingly prognosis of patients of this category. Keywords: chronic hepatitis C, autoimmune thireoiditis, antiviral therapy.     Резюме Цель работы - подобрать эффективную и безопасную терапию для лечения хронического гепатита С, ассоциированного с аутоиммунным тиреоидитом. Исследования проходили на базе различных больниц г. Одессы в течение 3 лет. Было обследовано 28 больных с хроническим НСV, ассоциированного с АИТ, в возрасте 18-53 лет. Исследовано, что добавление фосфоглива к безопасной противовирусной терапии хронического гепатита С, ассоциированного с аутоиммунным тиреоидитом, значительно улучшает эффективность лечения, а именно - клиническое течение заболевания, динамику лабораторных показателей (печеночных проб и данных тиреоидной панели), вирусологический ответ в виде уменьшения вирусологической нагрузки РНК HCV, динамику ультразвуковой структуры органов брюшной полости и щитовидной железы и соответственно прогноз больных данной категории. Ключевые слова: хронический гепатит С, аутоиммунный тиреоидит, противовирусная терапия.